Pengembangan Sistem Informasi Logistik Berbasis Web Dengan Fitur BAST Menggunakan Metode Waterfall - Hamid Abdul Rozak; Giat Karyono (Institut Teknologi Garut, 2026)
The logistics information system at Universitas Amikom Purwokerto does not yet provide a digital Handover Report (BAST) feature. This study develops a BAST module integrated into a web-based logistics system using the Laravel framework and MySQL through the Waterfall method. The BAST feature is designed to be integrated with goods transaction data through a transactional checklist mechanism, allowing users to prepare, save, and print documents without manually re-entering data. Testing was conducted through Black Box Testing with 7 test scenarios and User Acceptance Testing (UAT) involving 2 users, covering aspects of functionality, ease of use, and document printing efficiency. All test scenarios were successfully executed according to requirements, and the system received good to very good ratings across all UAT aspects, indicating that the integration of the BAST feature can significantly improve the efficiency of logistics administration. Future research is recommended to use a more standardized usability measurement method, such as the System Usability Scale (SUS).